Trunk muscle activation during movement with a new exercise device for lumbo‐pelvic reconditioning. Issue 6 (21st March 2017) - Weber, Tobias; Debuse, Dorothée; Salomoni, Sauro E.; Elgueta Cancino, Edith L.; De Martino, Enrico; Caplan, Nick; Damann, Volker; Scott, Jonathan; Hodges, Paul W
Abstract: Gravitational unloading leads to adaptations of the human body, including the spine and its adjacent structures, making it more vulnerable to injury and pain. The Functional Re‐adaptive Exercise Device (FRED) has been developed to activate the deep spinal muscles, lumbar multifidus (LM) and transversus abdominis (TrA), that provide inter‐segmental control and spinal protection. The FRED provides an unstable base of support and combines weight bearing in up‐right posture with side alternating, elliptical leg movements, without any resistance to movement. The present study investigated the activation of LM, TrA, obliquus externus (OE), obliquus internus (OI), abdominis, and erector spinae (ES) during FRED exercise using intramuscular fine‐wire and surface EMG. Nine healthy male volunteers (27 ± 5 years) have been recruited for the study. FRED exercise was compared with treadmill walking. It was confirmed that LM and TrA were continually active during FRED exercise. Compared with walking, FRED exercise resulted in similar mean activation of LM and TrA, less activation of OE, OI, ES, and greater variability of lumbo‐pelvic muscle activation patterns between individual FRED/gait cycles. These data suggest that FRED continuously engages LM and TrA, and therefore, has the potential as a stationary exercise device to train these muscles. Abstract : In this study, a novel exercise device for lumbo‐pelvic reconditioning was tested. Intramuscular EMG recordings of lumbo‐pelvic muscles suggest that the device has the potential to be used as a stationary tool to train important lumbo‐pelvic muscles. It may therefore be used to complement exercise programs to rehabilitate from lumbo‐pelvic muscle atrophy and dysfunction.